A CONCEPTUAL FRAMEWORK OF MALAYSIA MADANI MILLENNIALS FINANCIAL LITERACY (M3-FLF) - Sahaida Laily Md Hashim; Nor Edi Azhar Mohamad; Normaisarah Abdul Manaf; Suzaida Bakar; Nor Salwati Othman; Nor Hamisham Harun (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
Personal bankruptcy is one of the major issues highlighted in the current era. The report by the Malaysian Department of Insolvency indicated there were 233,483 bankruptcy cases reported until December 2023, while people aged 25 to 44 years old contributed about 56.99% to bankruptcy cases. According to a report published by the OECD in 2017, the main reason for the rise in bankruptcy is the lower level of financial literacy. In addition, the actual importance of financial literacy was raised during the recent economic slowdown triggered by the coronavirus disease (COVID-19) pandemic. Even though prior literature has linked financial literacy to financial inclusion, there are scanty empirical studies that examine the financial literacy of the millennials, especially in developing countries like Malaysia, and support the slogan of our Prime Minister, ’Malaysia MADANI’. However, no research has attempted to model and validate the Malaysia MADANI Millennials Financial Literacy Model. Hence, this study aims to capture the best-fit framework for the Malaysia MADANI Millennials Financial Literacy (M3-FLF) by integrating the technology acceptance theory. This paper is based on a literature review of journals on financial literacy, financial attitude, financial knowledge, financial skill, financial behavior and financial technology along with Theory Acceptance Model (TAM). Malaysian Millennials, those born between 1981 and 1996 and now aged between 28 and 43 years old. The outcome of this study will complement the Malaysia National Strategy for Financial Literacy 2019–2023, Malaysia MADANI’s directions to the Prime Minister, and support Social Development Growth for Societal Harmony and Happiness. Therefore, M3-FLF acts as a significant tool to signal the policymaker and provide self-awareness monitoring for individuals to help the future millennials navigate their financial well-being.